Africa Diary: News from the continent - Nicol, Martin (New Agenda: SA Journal of Social and Economic Policy, 2025)
Broadcast journalist Blessed Mhlanga was jailed in Harare, Zimbabwe on charges of incitement. He had interviewed a disgruntled war veteran who had called on President Emmerson Mnangagwa to resign, accusing him of nepotism, corruption and failing to address economic issues. Mnangagwa says he will step down in 2028 after two presidential terms. However there have been calls for him to stay on to fully implement his “Vision 2030,” based on “Democratic Principles, Rule of Law and Property Rights,” which aims to transform the country into an upper-middle-income economy by this date.